Determination of destruction conditions for substrates of flexible printed structures - Nevliudov, I. Sh.; Zharikova, I.; Novoselov, S.; Nevliudova, V. (Primedia eLaunch, 2022)
The results of the destruction conditions determination for polyimide substrates for electronic products are presented. The breakdown voltage for different operating conditions of the FPS has been determined. Using a tensile testing machine, critical levels of mechanical impact on FPS during their operation, which can lead to the destruction of polymer substrates, as well as of printed conductors on them, have been determined.
Keywords: flexible printed structures; destruction; polyimide; robotic mobile platforms; deformation; electric breakdown; experimental stand; tensile testing machine